189k views
2 votes
Solve for x. Show each step please . Circle your final answer.
2(8-12x)+8x= -25x+52

1 Answer

4 votes

Answer:

x = 4

Explanation:

Step 1: Simplify both sides of the equation.

2(8−12x)+8x=−25x+52

(2)(8)+(2)(−12x)+8x=−25x+52(Distribute)

16+−24x+8x=−25x+52

(−24x+8x)+(16)=−25x+52(Combine Like Terms)

−16x+16=−25x+52

−16x+16=−25x+52

Step 2: Add 25x to both sides.

−16x+16+25x=−25x+52+25x

9x+16=52

Step 3: Subtract 16 from both sides.

9x+16−16=52−16

9x=36

Step 4: Divide both sides by 9.

9x/9 = 36/9

x = 4

User MendyK
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.